Diálogo interétnico na escola : a implementaçãoda Lei 11.645/08 em Maringá/PR - Mori, Verônica Yurika (2012)
The difficulty in the school context in relation to the appreciation of cultural diversity in their midst has been constantly discussed by theorists from different backgrounds. In a way, we can see in the formulation of laws and educational advice an attempt to make you study, learn and disseminate knowledge and practices of ethnic minorities who were oppressed and exploited during the colonization process, there is an appreciation of the Brazilian cultural heterogeneity . However, it is assumed that efficient and effective actions to overcome these difficulties have not yet been addressed. This is because the school system has spread a knowledge of cultural and social nature Eurocentric, and that does not dialogue with other cultural knowledge. We view this statement when we face the difficulties that individuals from indigenous communities have access, stay in school and completion of the national society as well as difficulties in access to goods produced by it. Assuming that studying Indian culture for the enhancement enables to improve the living conditions of these individuals and also the recovery of any distinction, whether ethnic, social or cultural, that because the knowledge and practices of indigenous communities were and are privileged object in formulation of theories that value the Other, this paper proposes a study on the implementation of Law No. 11.645/08. This makes it mandatory to introduce the theme "Indigenous" in the official curriculum of the Basic Education Network.